Pyrolytic Conversion of Waste High-Density Polyethylene to Wax: Temperature Optimization and Characterization of Wax - Panda, Achyut Kumar; Mahapatra, Pabitra Mohan (Fine Chemical Engineering, 2024)
The formation of wax from waste high-density polyethylene by thermal decomposition through pyrolysis is examined in this work. To get wax from waste high-density polyethylene, the thermal cracking reaction is run in a semi-batch pyrolysis reactor at 550 °C, 600 °C, and 650 °C. The yield percentage, melting point, specific gravity, and penetration degree of wax varied depending on the temperature. At 600 °C, waste high-density polyethylene yielded the highest wax output (87.25%) with a 0.7768 specific gravity, a 59 °C melting point, and an 81.8 mm penetration degree. The fourier transform infrared spectroscopy (FTIR) analysis concluded the presence of aliphatic hydrocarbon compounds (alkane, alkene, alcohol, and cycloalkane), which is also confirmed by gas chromatography-mass spectrometry (GC-MS) analysis. The innovation in this study lies in the systematic exploration and optimization of temperature conditions for wax production from waste high-density polyethylene (HDPE) bottles.